Spectroscopic behavior, FMO, NLO and substitution effect of 2-(1H-Benzo[d]imidazole-2-ylthio)-N-o-substituted-acetamides: Experimental and theoretical approach. (December 2019) - Arif, Ali Muhammad; Yousaf, Afifa; Xu, Hong-liang; Su, Zhong-Min
Abstract: The benzimidazole-based derivatives2a-c were designed and synthesized via C–N coupling reaction and experimentally characterized by infrared spectroscopy (FT-IR), nuclear magnetic resonance ( 1 H NMR) spectroscopy and mass spectrometry (MS). The observed and calculated FT-IR frequencies correspond to CO stretching of amide group are depicted at 1657, 1672 and 1682, 1689 and 1699, 1682 for2a, 2b and2c respectively and are in good agreement. The synthesized compounds2a-c exhibit non-linear optical response with the first hyperpolarizability ( β 0 ) at 783, 1550 and 694 au, respectively. Due to the presence of electron withdrawing –NO2 on the primary amine of2b, the β 0 value is estimated at 1550 au, which reduces the energy barrier hence increasing the β 0 value, with maximum UV–vis absorption at 224 nm with TD-DFT method. The opposite behavior is demonstrated by the electron donor –OCH3 substituent. This study of NLO responses would be beneficial to the development of high-performance NLO materials. Graphical abstract: Three novel benzimidazole-based derivatives were designed and synthesized, which shows enhanced NLO responses and larger excitations with different electron donating/withdrawing groups substitution.Image 1 Highlights: Three novel benzimidazole-based derivatives2a, 2b and2c were characterized by FT-IR, 1 H NMR and mass spectrometry (MS). The synthesized compounds2a-c exhibit non-linear optical response with β 0 values at 783, 1550 and 694 au, respectively. The electron donating/withdrawing effects were studied through three different substituents i.e., –CH3, –OCH3 and –NO2 . The TD-DFT studies reveal that2b with –NO2 substitution exhibit obvious red shift with UV–vis absorption at 224 nm.